Malignant tumour arising in mature ovarian teratoma - Haqaue, WS; Alam, M; Islam, SMJ; Karim, MI; Yeasmin, S; Ahmed, I (Journal of Armed Forces Medical College, Bangladesh, 2013)
DOI: http://dx.doi.org/10.3329/jafmc.v8i1.13535 JAFMC Vol.8(1) 2012 pp.25-29